MECHANISMS FOR DEVELOPING STUDENTS CREATIVE AND CRITICAL THINKING THROUGH THE PROBLEM-BASED LEARNING APPROACH. (Ta'limning zamonaviy transformatsiyasi, 2025)
ANNOTATION. Problem-Based Learning (PBL) is an instructional methodology that encourages students to learn through the exploration of complex, real-world problems. This approach not only enhances knowledge acquisition but also fosters creative and critical thinking skills. This annotation outlines the mechanisms through which PBL facilitates these cognitive skills, highlighting its effectiveness in educational settings. Problem-Based Learning is an effective approach for developing students' creative and critical thinking skills. By engaging with complex problems, students learn to think independently, collaborate with peers, and apply their knowledge in innovative ways. The mechanisms inherent in PBL not only prepare students for academic success but also equip them with essential skills for their future professional lives.